Training on Climate-Smart Agriculture to Strengthen the Capacity of ASARECA-Member National Agricultural Research Institutes - Osumba, Joab; Recha, John W.M.; Amony, Blaise; Okonya, Joshua Sikhu; Barungi, Julian; Warinda, Enock (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
ASARECA is implementing the AICCRA project that has synergy with a project titled “Comprehensive Africa Agriculture Development Programme ex-pillar IV (CAADP-XP4)”. Implementation of this 5-year CAADP-XP4 project started in 2019 and is part of the European Union’s (EU) Development Smart Innovation through Research in Agriculture (DeSIRA) initiative. The project is expected to deliver five (5) key outputs namely: (i) Strengthened capacities of ASARECA and partner organizations in competencies required for successful implementation of the CAADP-XP4 project; (ii) Multistakeholder partnerships for innovation established and in operation; (iii) Policies in support of climate-relevant agriculture and food systems transformation formulated, investments increased, advocacy and market linkages strengthened; (iv) Knowledge management and communication systems for decision-making and sharing of innovation and for advocacy related to climate-relevant agriculture transformation established; and (v) Enhanced planning, coordination, monitoring, evaluation, learning, and reporting. The training in CSA were organized under the auspices of ASARECA’s AICCRA and CAADP-XP4 projects. The training contributed to AICCRA activity 2.3.3 on Building capacity of public and private sector next users to support implementation of CSA technology packages in focus countries. The CSA training also contributed to CAADP-XP4 project activity area 1.1 that focuses on Strengthening the internal capacities of ASARECA and its regional and country level partners.